Model Public Private Partnership Penyediaan Infrastruktur Pelayanan Publik: Pengalaman Indonesia dan India - Muhammad Tang Abdullah (Publik : (Jurnal Ilmu Administrasi), 2020)
This study is based on the fact that there are several weaknesses that the government has in the provision of public service infrastructure, both in Indonesia and India. Some of these weaknesses include limited capacity of apparatus resources, budget shortages, management and technology weaknesses in the provision of public service infrastructure. This article aims to see how a public private partnership is conceptually and how the experiences of the Indonesian and Indian states in putting this concept into practice. This study uses qualitative research methods with library research techniques. Literature study is applied with data analysis techniques in several stages. Through this literature study method, it was found that public private partnership is strongly associated with the concept of new public management and governance. There are many forms of public private partnership such as BOT (Build Operate and Transfer), BT (Build and Tranfer), BTO (Build, Transfer, and Operate), BLT (Build, Lease, and Transfer), BOO (Build, Own, and Operate), ROO (Rehabilitate, Own, and Operate), ROT (Rehabilitate, Own, and Transfer), DOT (Develop, Operate, and Transfer), and CAO (Contract, Add, and Operate). But the overall form is essentially aimed at providing infrastructure and public services can be more efficient, effective and economical. In practice, both in Indonesia and India, has had a noticeable effect such as the opening of new jobs for residents because this public private partnership has long been applied in various development sectors, especially in the service of basic community needs, such as education, health, transportation, public housing, social services, and clean water supply.Kajian ini didasarkan pada fakta adanya beberapa kelemahan yang dimiliki oleh pemerintah dalam penyediaan infrastruktur pelayanan publik, baik di Indonesia maupun India. Beberapa kelemahan tersebut meliputi keterbatasan kapasitas sumberdaya aparatur, kekuragan anggaran, kelemahan manajemen dan teknologi dalam pengadaan infrastruktur pelayanan publik. Artikel ini bertujuan untuk melihat bagaimana public private partnership secara konseptual dan bagaimana pengalaman negara Indonesia dan India dalam mempraktekkan konsep tersebut tersebut. Kajian ini menggunakan metode penelitian kualitatif dengan teknik studi kepustakaan. Studi kepustakaan diterapkan dengan teknis analisis data dalam beberapa tahap. Melalui metode studi kepustakaan ini ditemukan bahwa public private partnership sangat terkait dengan konsep new public management dan governance. Terdapat banyak bentuk public private partnership seperti BOT (Build Operate and Transfer), BT (Build and Tranfer), BTO (Build, Transfer, and Operate), BLT (Build, Lease, and Transfer), BOO (Build, Own, and Operate), ROO (Rehabilitate, Own, and Operate), ROT (Rehabilitate, Own, and Transfer), DOT (Develop, Operate, and Transfer), dan CAO (Contract, Add, and Operate). Namun keseluruhan bentuk tersebut pada hakekatnya bertujuan agar penyediaan infrastruktur dan pelayanan publik bias lebih efisien, efektif dan ekonomis. Dalam prakteknya baik di Indonesia maupun India telah memberi efek yang nyata seperti terbukanya lapangan kerja baru bagi warga karena public private partnership ini sudah sejak lama diterapkan dalam berbagai sektor pembangunan, terutama pada pelayanan kebutuhan dasar masyarakat, seperti pelayanan pendidikan, kesehatan, transportasi, perumahaan rakyat, soaial, dan penyediaan air bersih.